Understanding Blockchain Adoption in SMEs : A Mixed-Method Study of Digital Transformation, Resilience, and Senior Leadership Support - Chakraborty, Debarun; Behl, Abhishek; Golgeci, Ismail; Nazrul, Asif (IEEE, 2025)
This article investigates the adoption of blockchain technology (BCT) by small- and medium-sized enterprises (SMEs), focusing on the interplay between digital transformation, market volatility, and organizational resilience. The goal of this article is to assess how perceived usefulness and perceived ease of use shape SMEs’ intention to adopt BCT. This article integrates the Technology Acceptance Model with the Dynamic Capabilities Theory and explores how perceived usefulness, ease of use, and resilience influence SMEs’ adoption intentions under the boundary conditions of senior leadership support (SLS). Conducted in India from November 2023 to February 2024, a mixed-method approach combining qualitative insights from interviews and case studies with quantitative analysis from survey data is employed to provide a comprehensive understanding of the factors driving or hindering BCT adoption. The findings also underscore the critical role of SLS in fostering resilience and guiding SMEs through the digital transformation process, highlighting the need for tailored strategies to support BCT integration in resource-constrained environments. This article contributes to bridging the knowledge gap on BCT's impact on SMEs, offering practical implications for entrepreneurs seeking to leverage BCT for competitive advantage amid volatility. This article reveals that SMEs’ successful adoption of BCT hinges not only on perceived usefulness and ease of use but also on the strategic alignment of digital capabilities with resilience-building efforts, particularly under strong SLS.
Keywords: Blockchain technology (BCT); digital transformation; intention to adopt; volatile; uncertain; complex; ambiguous (VUCA); small and medium-sized enterprises